Memristors promise more precise and affordable neuroprosthetics.
In a new paper, researchers from the University of Southampton, UK and members of the EU-funded RAMP project, have demonstrated how memristors could help aid the development of more precise and affordable neuroprosthetics and bioelectric medicines.